Implementasi Sistem Just In Time (JIT) Pada Persediaan Bahan Baku Untuk Memenuhi Kebutuhan Produksi Di PT Yakult Indonesia Persada Cabang Mojokerto - Vina Safitri; Kristiana Sri Utami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research examines the implementation of the Just In Time (JIT) system for raw material inventory at PT Yakult Indonesia Persada, Mojokerto Branch. The application of JIT aims to enhance operational efficiency and company profitability by reducing inventory costs and optimizing production processes. This study references previous research that indicates JIT can increase the contribution margin per unit, reduce ordering and storage costs, and improve production efficiency. The findings show that implementing JIT at PT Yakult Indonesia Persada can reduce waste, enhance operational efficiency, and ensure the availability of raw materials according to production needs. Therefore, JIT is a suitable strategy to improve the company's competitiveness and business sustainability.